Child feeding practices and diarrheal disease among children less than two years of age of the nomadic people in Hadaleala District, Afar Region, Northeast Ethiopia - Zemichael Gizaw; Wondwoson Woldu; Bikes Destaw Bitew (BMC, 2017)
Abstract Background Diarrhea is a serious public health problem in Ethiopia. It is responsible for 24-30% of all infant deaths and there is a lack of evidence on the health burdens among the nomadic people. This study was therefore designed to assess the prevalence of diarrhea among children less thanvtwo year's of age and its association with feeding practices among the nomadic people in Hadaleala district, northeast Ethiopia. Methods A cross-sectional study was conducted in Hadaleala district. A total of 367 children less than two years of age were included using the multistage cluster sampling technique. Data were collected by a structured questionnaire. Multivariable binary logistic regression analysis was used to identify variables associated with diarrheal disease. Results The prevalence of diarrhea among children less than two year's of age during the two week period was 31.3% (95% CI, 25.9, 36.1%). Diarrhea occurrence was associated with; children aged between 6-11 months (AOR 6.28, 95% CI, 3.00, 13.12), aged between 12-24 months (AOR 6.21, 95% CI, 3.13, 12.30), illiterate mothers (AOR 6.61, 95% CI, 2.27, 19.21), delay to initiate early breastfeeding for children aged less than six months (AOR 9.13, 95% CI, 1.78, 46.72), children less than six months of age not currently exclusively breastfed (AOR 13.33, 95% CI, 1.59, 112.12), delay to initiate early breastfeeding for children aged 6-24 months (AOR 2.87, 95% CI, 1.49, 5.51), no breastfeeding at the time of the survey (AOR 3.51, 95% CI, 1.57, 7.82), children aged 6-24 months who didn't exclusively breastfeed in the first six months (AOR 19.24, 95% CI, 8.26, 44.82), consuming uncooked foods (AOR 6.99, 95% CI, 2.89, 16.92), not eating cooked foods immediately after cooking (AOR 3.74, 95% CI, 1.48, 9.45), hand washing with only water (AOR 24.94, 95% CI, 6.68, 93.12), and rotavirus vaccination (AOR 0.09, 95% CI, 0.03, 0.29). Conclusions The prevalence of diarrhea among children less than two year's of age in Hadaleala district was high. To prevent diarrhea, the mothers should start breastfeeding early and practice exclusive breastfeeding. Moreover, mothers should improve the hygiene of supplementary foods.